empoderamiento de los derechos de las mujeres del sitio san jacinto: desde la perspectiva del trabajador social, 2023 - Toro Ruiz, Nathaly Silvana; Shingre Ramirez, Carelyn Analia (Machala, 2025)
The main objective of this thesis is to promote the empowerment and rights of women in the San Jacinto Site, seeking to promote gender equality and the ctive participation of women in decision-making. From the perspective if Social Work, it is intended to address the reality of these women and contribute to their autonomy, facilitating an environment where ther cn fully exercise their rights. The method for carrying out the diagnosis is based on a qualitative approach, which allowed us to understand and analyze the experiences of women in their socual context. Througt various techniques such as: participant obervation, interviews and home visits, where we sought to obtain a deeper understanding of the reality experienced by the participants of this community. Our research sample in made up of 50 women from the site, of which 20 were selected as a random sample due to their characteristics. Two important instruments were used to be able to approach the research: the structured interview and the observation guie, which allowed ud to collect trurhful data, facilitating a closer interaction with women, thus having direct contact and knowing more about their reality. The results obtanied fron our research indicated that women in this community, despite having a favorable physical enviorenment, lack information about their rights. This lack of knowledge limits their ability to exercise them, which affects their autonomy in decision-making. Howere, a notable willingness was observerd among the participants to learn and participate in activities that allow them to know and use their rights. For this reason, we can conclude and suggest various recommendations to address the identified situation It is important to organize workshops tha provide women`s rights and establish community forums that allow the exchange of experiences. In addition, use the media to disseminate information about the same. These initiatives can contribute to creating a more equitable environment, where women in San Jacinto feel empowered to exercise their rights and autonomy.
El presente trabajo de titulación tiene como objetivo principal promover el empoderamiento y los derechos de las mujeres en el Sitio San Jacinto, buscando fomentar la equidad de género y la participación activa de las mujeres en la toma de decisiones. Desde la perspectiva del Trabajo Social, se pretende abordar la realidad de estas mujeres y contribuir a su autonomía, facilitando un entorno donde puedan ejercitar sus derechos plenamente. El método para realizar el diagnóstico se adopta al enfoque cualitativo, que permitió comprender y analizar las experiencias de las mujeres en su contexto social. A través de diversas técnicas como: la observación participante, entrevista y la visita domiciliaria, donde se buscó obtener una comprensión más profunda a la realidad vivida por las participantes de esta comunidad. Dentro de nuestra muestra de investigación está compuesta por 50 mujeres del sitio, de las cuales se seleccionaron 20 como una muestra aleatoria debido a sus características. Se utilizaron 2 instrumentos importante para poder abordar la investigación como: la entrevista estructurada y la guía de observación, lo que permitió recolectar datos verídicos, facilitando una interacción más cercana a las mujeres, teniendo así contacto directo y conocer más su realidad. Los resultados obtenidos de nuestra investigación, indicaron que las mujeres de esta comunidad, a pesar de tener un entorno físico favorable, carecen de información sobre sus derechos, este desconocimiento limita su capacidad para poder ejércelos, lo que afecta su autonomía en la toma de decisiones. Sin embargo, se observó una disposición notable entre las participantes para aprender y participar en actividades que les permitan conocer y hacer uso de sus derechos. Por tal motivo, se puede concluir y sugerir diversas recomendaciones para abordar la situación identificada. Es importante organizar talleres que proporcionen los derechos de las mujeres y establecer foros comunitarios que permitan el intercambio de experiencias, Además, utilizar medios de comunicación para difundir información sobre la misma. Estas iniciativas pueden contribuir a crear un entono más equitativo, donde mujeres de San Jacinto se sientan empoderadas para ejercer sus derechos y autonomía. .
Keywords: EMPODERAMIENTO; DERECHOS DE LAS MUJERES; EQUIDAD DE GENERO; PARTICIPACION COMUNITARIA.